(untitled) - Stanley Karnow (New York, 1991)
The book clarifies, analyzes, and demystifies the tragic ordeal of the Vietnam war. Free of ideological bias, profound in its understanding, and compassionate in its human portrayals, it is filled with fresh revelations drawn from secret documents and from exclusive interviews with the participants - French, American, Vietnamese, Chinese: diplomats, military, commanders, high government officials, journalists, nurses, workers, and soldiers. The book puts events and decisions into such sharp focus that we come to understand - and make peace with - a convulsive epoch of our recent history
Keywords: united states - history - 1945-,vietnam - history - 1858-1945,vietnam - history - 1945-1975,vietnamese conflict, 1961-1975,vietnamese conflict, 1961-1975 - united states